Analysis of Religious Court Decisions in Resolving Inheritance Disputes Still Under Collateral a Maqashid Syariah Perspective - Abdulsiddik, Yusep; Roza Elsera, Utari; Husni, Alfi (Yayasan Lembaga Studi Makwa, 2024)
Inheritance law governs the transfer of wealth left by a deceased person and its impact on the heirs. Issues often arise regarding the management and continuation of the rights and obligations of the deceased. This study aims to describe inheritance cases still under collateral at the Religious Court of Talu and to analyze the judicial decision from the perspective of Maqashid Syariah. The study employs two approaches: the statute approach and the analytical approach. The research findings show that the judge granted the inheritance dispute still under collateral with case registration number 559/Pdt.G/2022/PA.Talu. This was due to the judge's application of